Analisis Upaya Pemerintah dalam Penerapan Pelayanan Kapal Melalui INAPORTNET (Studi: Kantor Kesyahbandaran dan Otoritas Pelabuhan Lhokseumawe di Provinsi Aceh - Iskandar, Iskandar; Hafni, Nur; Abubakar, Muhammad Bin (Program Magister Administrasi Publik, 2023)
Shipping plays a crucial role in the efforts to achieve national objectives outlined in Pancasila and the Republic of Indonesia's 1945 Constitution. Naturally, the government plays a crucial role in ensuring that everything runs smoothly in an effort to realize this situation. through government agencies, specifically the Harbormaster Office and the Lhokseumawe Class IV Port Authority. This study aims to examine and demonstrate how the Inaportnet application's implementation of policies pertaining to shipping authorization management is carried out. The descriptive design of this study is combined with a qualitative research approach. A research approach known as qualitative research approaches the world as a whole through the lens of holistic, complex, dynamic, meaningful, and inductive reasoning. The Lhokseumawe Class IV Harbormaster and Port Authority Office has implemented the Policy for Issuing Sailing Approval Letters (SPB) in accordance with applicable regulations, but there are still a few obstacles in the way. The applicant's lack of comprehension of the procedures for issuing sailing approval letters (SPB) is one of the obstacles in issuing sailing approval letters (SPB) at Class IV Lhokseumawe Harbor Masters and Port Authority offices. IV Lhokseumawe is attempting to keep providing service users with information so that they can comprehend the procedure for issuing a Sailing Approval Letter (SPB). An online system should be used to carry out Syahbandar's responsibilities for issuing sailing approval letters (SPB), so that there are no signs of extortion